Разработка процесса глубокого плазменного травления кремния для технологии трехмерной интеграции кристаллов - Golishnikov, А. А.; Putrya, M. G. (PE "Politekhperiodika", Book and Journal Publishers, 2014)
Plasma etch process for thought-silicon via (TSV) formation is one of the most important technological operations in the field of metal connections' creation between stacked circuits in 3D assemble technology. TSV formation strongly depends on parameters such as Si-wafer thickness, aspect ratio, type of metallization material, etc. The authors investigate a deep silicon plasma etch process for formation of TSV with controllable profile. The influence of process parameters on plasma etch rate, silicon etch selectivity to photoresist and the structure profile are researched in this paper. Technology with etch and passivation steps alternation was used as a method of deep silicon plasma etching. Experimental tool «Platrane-100» with high-density plasma reactor based on high-frequency ion source with transformer coupled plasma was used for deep silicon plasma etching. As actuation gases for deep silicon etching were chosen, the following gases: SF6 was used for the etch stage and CHF3 was applied on the polymerization stage. As a result of research, the deep plasma etch process has been developed with the following parameters: silicon etch rate 6 µm/min, selectivity to photoresist 60 and structure profile 90±2°. This process provides formation of TSV 370 µm deep and about 120 µm in diameter.